Pengaruh Tata Tertib Dan Keteladanan Guru Terhadap Kedisiplinan Belajar Siswa Pada Pembelajaran PAI Di SMA Negeri 1Tebing Syahbandar - Utami, Lisa; Nasution, Herry Syahbannuddin; Parinduri, Sari Atika (STAI Tebing Tinggi Deli, 2024)
The Influence of Teacher Rules and Example on Student Learning Discipline in PAI Learning at SMA Negeri 1 Tebing Syahbandar, Tebing Syahbandar District, Serdang Bedagai Regency. Department of Islamic Religious Education, Islamic College (STAI) Tebingtinggi Deli. The aims of this research are: (1) To determine the significant influence of rules and regulations on the learning discipline of SMA N 1 Tebing Syahbandar students, (2) To determine the significant influence of teacher example on the learning discipline of SMA N 1 Tebing Syahbandar students, (3) To determine the significant influence between rules and teacher example on the learning discipline of SMA N1 Tebing Syahbandar students. The subjects in this research were class XII students at SMA Negeri 1 Tebing Syahbandar, totaling 143 students (respondents). The test results for the discipline variable show a tcount value of 1.333 and a sig value of 0.185. Where tcount > ttable (2.421 > 1.655) and the sig value (0.185 > 0.05). So according to the criteria for partial hypothesis testing, the first hypothesis is accepted, which means that there is a positive and significant influence between rules and regulations on student learning discipline at SMA N 1 Tebing Syahbandar. The results of the T test for the teacher exemplary variable show a t-count of 7.909 and a sig value of 0.000. Where tcount > ttable (7.909 > 1.655) and the sig value (0.000 < 0.05) then these results indicate that there is a positive and significant influence between teacher example on student learning discipline at SMA N 1 Tebing Syahbandar. The F test results obtained Fcount of 38,283 with a probability value (sig) = 0.000. The value of Fcount (38,283) > Ftable (3.06) and the sig value is smaller than the probability value of 0.05 or the value of 0.000 < 0.05. This proves that the hypothesis